Akademik Ivan Pavlov . Academic Ivan Pavlov - Roshal, Grigory (Lenfilm, 1949)
Film about Ivan Petrovich Pavlov, physiologist, researcher into the nervous system and reflexes, Noble prizewinner. The film tells of Pavlov's scientific career, his discoveries and their impact on medicine and psychology. Pavlov is depicted as a man before his time, subject to the ridicule of the hidebound scientific establishment.